MATHEMATICAL SIMULATION OF USER SATISFACTION PARAMETERS AND ORGANIZATION MANAGEMENT QUALITY SYSTEM EFFICIENCY - Robert R. Lazurenko; Irina G. Koshlyakova; Tatiana V. Rastrygina; Anastasia A. Berezina (Advanced Engineering Research)
The problem of mathematical model in complexation of production, work, services quality parameters is solved. Distribution of rank weights among and within quality parameters groups is considered. Distribution of quality parameters is described by the hyperbolic rank function. The method permits to plan work on quality parameters improvement with the aim of user satisfaction parameters growth.